Clonal-aggregative multicellularity tuned by salinity in a choanoflagellate - Núria Ros-Rocher; Josean Reyes-Rivera; Uzuki Horo; Chantal Combredet; Yeganeh Foroughijabbari; Ben T. Larson; Maxwell C. Coyle; Erik A. T. Houtepen; Mark J. A. Vermeij; Jacob L. Steenwyk; Thibaut Brunet (Nature, 2026)
Abstract Multicellularity evolved independently multiple times in eukaryotes 1–4 . Two distinct mechanisms underpin multicellularity 5 : clonality (serial cell division without sister-cell separation) and aggregation (whereby independent cells assemble into a multicellular entity). Clonal and aggregative multicellularity are traditionally considered to be mutually exclusive 1,6–8 , with rare exceptions 9 , and evolutionary hypotheses have addressed why multicellularity might diverge towards one or the other extreme 3,4 . Both animals and their sister group, the choanoflagellates, are currently known to acquire multicellularity only clonally 4,10,11 . Here we show that the choanoflagellate Choanoeca flexa 12 forms motile and contractile cell monolayers (sheets) through multiple mechanisms— C. flexa sheets can form purely clonally, purely aggregatively or through a combination of both processes. We characterize the life history of C. flexa in its natural environment—ephemeral splash pools on the island of Curaçao—and show that C. flexa undergoes reversible transitions between unicellularity and multicellularity during evaporation–refilling cycles. Different splash pools house genetically distinct strains of C. flexa and kin recognition constrains aggregation between them. We show that clonal-aggregative multicellularity is a versatile strategy for the robust establishment of multicellularity in this variable and fast-fluctuating environment. Our findings challenge former generalizations about choanoflagellates and expand the option space of choanozoan multicellularity.